2022
DOI: 10.1002/aid2.13306
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center retrospective study comparing 1‐day and 3‐day low‐residue diets for bowel preparation

Abstract: A low-residue diet (LRD) is recommended as part of bowel preparation before a colonoscopy. However, the optimal duration of the LRD is unclear. A retrospective cross-sectional study was therefore conducted at E-Da Dachang Hospital. We compared bowel preparations using the Aronchick score and other quality metrics during two consecutive periods: May 2019 to December 2019 (3-day LRD) and January 2020 to August 2020 (1-day LRD). A total of 2823 patients were enrolled (1592 in the 3-day LRD group and 1231 in the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
4
5
0
Order By: Relevance
“…Notably, the 1‐day LRD group had a higher detection rate of advanced adenomas (5.9% vs. 3.4%, P = .002) and sessile serrated lesions (8.9% vs. 6.3%, P = .014). The choice of laxatives and the use of supplemental laxatives did not impact the quality of bowel preparation 14 . These findings align with updated guidelines and provide valuable insights for clinicians 9,11,14 …”
supporting
confidence: 70%
See 3 more Smart Citations
“…Notably, the 1‐day LRD group had a higher detection rate of advanced adenomas (5.9% vs. 3.4%, P = .002) and sessile serrated lesions (8.9% vs. 6.3%, P = .014). The choice of laxatives and the use of supplemental laxatives did not impact the quality of bowel preparation 14 . These findings align with updated guidelines and provide valuable insights for clinicians 9,11,14 …”
supporting
confidence: 70%
“…The choice of laxatives and the use of supplemental laxatives did not impact the quality of bowel preparation 14 . These findings align with updated guidelines and provide valuable insights for clinicians 9,11,14 …”
supporting
confidence: 70%
See 2 more Smart Citations
“…Two articles were not included in our analysis because they were not RCTs, but their conclusions are basically consistent with those of our metaanalysis. 23,24 A study containing post hoc analysis of a 1-day versus 3-day LRD suggested that a well-structured 3-day LRD is not superior to the 1-day LRD in terms of colon cleansing quality in patients with risk factors of poor bowel cleansing. 23 In a single-center retrospective study comparing 1-day and 3-day LRD for bowel preparation, a real-world study was conducted on LRD with different durations and found a 1-day LRD led to bowel preparation similar to that achieved through a 3-day LRD regardless of the type of primary cleansing agent or the use of supplemental laxatives.…”
Section: Discussionmentioning
confidence: 99%